Assessment and Management of Depression and Anxiety in Children and Adolescents with Epilepsy. (2nd May 2019) - Plevin, David; Smith, Nicholas
Abstract : Anxiety and depression in children and adolescents with epilepsy are common comorbidities which place a significant burden on patients and families and complicate the clinical management of epilepsy. This paper presents a narrative review on the aetiology, phenomenology, assessment, and management of depression and anxiety among paediatric patients with epilepsy. The recognition of affective comorbidity in paediatric epilepsy is limited at present, and the contributory role of antiepileptic medication towards such comorbidity must be considered by clinicians.